2011
DOI: 10.1111/j.1399-3038.2010.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic diseases among very preterm infants according to nutrition after hospital discharge

Abstract: To determine whether a cow's milk-based human milk fortifier (HMF) added to mother's milk while breastfeeding or a cow's milk-based preterm formula compared to exclusively mother's milk after hospital discharge, increases the incidence of developing allergic diseases among very preterm infants (VPI) during the first year of life. Of a cohort of 324 VPI (gestational age 24-32 wk), the exclusively breastfed VPI were shortly before discharge randomized to breastfeeding without fortification or supplementing with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
2
28
0
1
Order By: Relevance
“…The relevant fact is that only 4.3% of patients with CMA were premature, and this figure is much lower than the proportion in the general population (13.2% in the control group). This fact has already been pointed out by Zachariassen et al [29] who, when studying the incidence of allergic disease in a cohort of extremely premature infants, did not find a single case of food allergy. The explanation for this is possibly immunological: the premature patient's immune system is most likely not developed enough to generate IgE-mediated reactions to allergens through the digestive tract, a fact that was already observed in a study published in 1975 by Rieger and Rothberg [42] in which it was found that up until 35-36 weeks newborns exposed to CMP are not able to generate specific IgE antibodies.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The relevant fact is that only 4.3% of patients with CMA were premature, and this figure is much lower than the proportion in the general population (13.2% in the control group). This fact has already been pointed out by Zachariassen et al [29] who, when studying the incidence of allergic disease in a cohort of extremely premature infants, did not find a single case of food allergy. The explanation for this is possibly immunological: the premature patient's immune system is most likely not developed enough to generate IgE-mediated reactions to allergens through the digestive tract, a fact that was already observed in a study published in 1975 by Rieger and Rothberg [42] in which it was found that up until 35-36 weeks newborns exposed to CMP are not able to generate specific IgE antibodies.…”
Section: Discussionmentioning
confidence: 62%
“…Other factors that have been studied are caesarean delivery [19,20,21,22,23] and perinatal exposure to small amounts of CMP [24,25,26,27], though the results are conflicting. Other factors such as duration of BF [14,28,29], prematurity, threatened premature delivery, preeclampsia [30], hypertension, gestational diabetes [31], and antibiotics [21] during labor have been much less studied. The purpose of this study is to analyze the impact different perinatal factors may have on the development of IgE-mediated CMA.…”
Section: Introductionmentioning
confidence: 99%
“…There do not appear to be consistent benefits of human milk in premature infants in relation to feeding tolerance, 19 time to full enteral feeding, 24 or allergic/atopic outcomes. 40 Providing human milk has been postulated to decrease parental anxiety, increase skin-to-skin contact and parent-infant bonding, but data to support these hypotheses are limited. The provision of human colostrum in the form of oral care for intubated premature infants has been proposed as a method of stimulating the oropharyngeal-associated lymphatic tissue and altering the oral microbiota, but data to support this intervention are lacking.…”
Section: Benefits Of Human Milk For Premature Infantsmentioning
confidence: 99%
“…In preterm‐born infants with BPD, no influence of increased intake of energy on respiratory outcomes has been found . Among non‐BPD preterm‐born infants, wheezing at 1 year of age was not associated with post‐discharge nutrition …”
Section: Introductionmentioning
confidence: 97%
“…18 Among non-BPD preterm-born infants, wheezing at 1 year of age was not associated with postdischarge nutrition. 19 Measurement of fractional exhaled nitric oxide (FeNO) is a noninvasive method to screen for airway inflammation in asthma. FeNO is synthesised and expressed by airway epithelial cells as an inflammatory response, and the value can be increased twofold-threefold in patients with asthma.…”
Section: Introductionmentioning
confidence: 99%